2022
DOI: 10.3390/ijerph191610228
|View full text |Cite
|
Sign up to set email alerts
|

Oral Lesions Following Anti-SARS-CoV-2 Vaccination: A Systematic Review

Abstract: Increasing evidence relate anti-SARS-CoV-2 vaccinations to orofacial adverse reactions, therefore, the present systematic review aimed to evaluate primary oral lesions diagnosed in adult subjects, following the WHO Emergency Use Listing approved and EMA authorized vaccines, also in relation to cases’ age, gender, comorbidities, and history of COVID-19, and in relation to vaccine type and doses. The study protocol, registered on PROSPERO (CRD42022339032) and compliant with the PRISMA statement, included an elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 52 publications
1
46
0
Order By: Relevance
“…Given the fortunately low but possible occurrence of oral lesions after anti-SARS-CoV-2 vaccination, pediatric dentists should be alert to such possible additional oral needs [ 22 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Given the fortunately low but possible occurrence of oral lesions after anti-SARS-CoV-2 vaccination, pediatric dentists should be alert to such possible additional oral needs [ 22 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…A similar estimate might also be computed for the progression of such diseases in periodontal subjects. Personalized prevention strategies may be even more relevant in those subjects considered at higher risk of periodontitis and peri-implantitis onset and progression, such as those suffering from comorbidities [ 4 , 10 , 14 , 15 , 30 , 33 , 78 , 79 , 80 ], especially diabetes [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, polysorbate 80 (PS80), a vaccine excipient preventing mRNA rapid degradation, was proven to cross‐react with polyethylene glycol, which is involved in delayed (>24 h) mucocutaneous lesions following mRNA‐based COVID‐19 vaccines (Hatami et al, 2021 ). Accordingly, Manfredi et al reported diffuse erythematous and ulcerative lesions in a subject vaccinated with mRNA BNT162b2 Comirnaty (Pfizer‐BioNTech) containing PS80 (Di Spirito, Amato, et al, 2022 ; Di Spirito, Pelella, et al, 2022 ).…”
mentioning
confidence: 99%
“…A further pathogenic hypothesis may be linked to the reactivation of herpes simplex virus type 1 and varicella‐zoster virus (Di Spirito, Amato, et al, 2022 ; Di Spirito, Pelella, et al, 2022 ; Shafie'ei et al, 2022 ), observed in oral mucosal and cutaneous adverse reactions. Both viruses are also involved in the genesis of erythema multiforme and Bell's palsy (Cirillo & Doan, 2022 ), the last seeming increasingly documented following mRNA and inactivated COVID‐19 vaccines compared with the background rate.…”
mentioning
confidence: 99%
See 1 more Smart Citation